Minuty poezii . Minuty poezii . Poetry Minutes . Минуты поэзии - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Pavel Bogdanov recites his poetry. Featured in the program: Bogdanov, Pavel (Poet) Поэт Павел Богданов читает свои стихи. В программе участвуют: Богданов, Павел (Поэт)